Glicerinas semipurificadas na alimentação de suínos - Gonçalves, Liliane Maria Piano (2012)
Four experiments were carried out to determine the nutritional value and to evaluate the performance of starting, growing and finishing pigs, fed with vegetables (SPGV) and mixed (SPGM) semipurified glycerins. In the Experiment I, a digestibility trial were carried out using 32 crossbreed piglets with initial body weight of 19.20 ± 1.52 kg, allotted in a completely randomized design. It were evaluated two types of semipurified glycerins (SPGV and SPGM), and three levels of glycerin in the basal diet (4, 8, and 12%). The experimental unit consisted of one piglet. The digestible (DE) and metabolizable (ME) energy values of glycerin were estimated by regression of DE and ME (Kcal/kg) intake associated with glycerin vs. glycerin intake (kg). The values (as-fed-basis) of DE and ME (Kcal/kg) obtained were: SPGV = 3,793 and 3,373; SPGM = 3,220 and 2,932, respectively. The results indicate that these two types of glycerin are highly available energy source for piglets feeding (15 - 30 Kg). In the Experiment II, were used 90 piglets with initial body weight of 15.27 ± 0.99 and final of 29.82 ± 3.02 kg), allotted in a completely randomized design in 2 x 4 + 1 factorial scheme, with two types of semipurified glycerin (SPGV and SPGM), four levels (3, 6, 9, and 12%), five experimental unit (pens) and two pigs per pen. Additionally it was formulated a control diet contain no glycerin (0%). There were no interaction among semipurified glycerins levels and types of semipurified glycerin. The regression analysis indicates no effects of semipurified glycerin inclusion on performance and plasmatic variables. The results of performance trial suggest that it is feasible to use up to 12% of both semipurified glycerins on starting piglet feeding. In the Experiment III, a digestibility trial were carried out using 32 crossbreed pigs with initial body weight of 45.08 ± 4.11 kg, allotted in a completely randomized design. It were used two different types of semipurified glycerin (SPGV and SPGM), and three levels of glycerin in the diet (6, 12, and 18%). The experimental unit consisted of one pig. The digestible (DE) and metabolizable energy (ME) values of glycerin were estimated by regression of DE and ME (Kcal/kg) intake associated with glycerin vs. glycerin intake (kg). The values, (as-fed-basis) of DE and ME (Kcal/kg) obtained were: SPGV= 3,777 and 2,731; SPGM = 3,090 and 2,210, respectively. The results indicate that these two types of glycerin are highly available energy source for growing-finishing pigs feeding (30 - 90 Kg). In the Experiment IV, 72 pigs whit initial body weight of 30.08 ± 1.65 kg an final of 60.58 ± 3.57 kg in the growing phase and 72 pigs whit initial body weight of= 60.83 ± 2.63 kg and final of= 93.79±5.72 in finishing phase, were allotted in a completely randomized design in 2 x 4 + 1 factorial scheme, with two types of semipurified glycerin (SPGV and SPGM), four levels (4, 8, 12 and 16%), resulting in eight replicates per treatment and one pig per experimental unit. Additionally it was formulated a control diet contain no glycerin (0%). At the end of the finishing phase all pigs were slaughtered to evaluate the quantitative and qualitative carcass traits. There were no interaction among inclusion levels and type of semipurified glycerin. The regression analysis indicates no effects of semipurified glycerin inclusion on performance, plasmatic variables and carcass traits (backfat thickness and loin depth). The performance results suggest that it is feasible to use up to 16% of vegetables and mixed semipurified glycerins on growing and finishing pig feeding, without impairing performance, plasmatic variables and carcass traits.